Filmes de metal-hexacianoferrato: Uma ferramenta em química analítica - De Mattos, Ivanildo Luiz [UNESP]; Gorton, Lo (FapUNIFESP (SciELO), 2001)
Chemically modified electrodes based on hexacyanometalate films are presented as a tool in analytical chemistry. Use of amperometric sensors and/or biosensors based on the metal-hexacyanoferrate films is a tendency. This article reviews some applications of these films for analytical determination of both inorganic (e.g. As3+, S2O3 2-) and organic (e.g. cysteine, hydrazine, ascorbic acid, gluthatione, glucose, etc.) compounds.
Metal-hexacyanoferrate films: A tool in analytical chemistry
Keywords: Biosensor; Metal hexacyanoferrate; Modified electrodes